1990
DOI: 10.1111/j.1558-5646.1990.tb05197.x
|View full text |Cite
|
Sign up to set email alerts
|

ENHANCEMENT OF INBREEDING DEPRESSION BY DOMINANCE AND SUPPRESSION IN IMPATIENS CAPENSIS

Abstract: Abstract. -We investigated the effect of intraspecific competition on the magnitude of inbreeding depression in Impatiens capensis by planting seeds from chasmogamous (CH) and cleistogamous (CL) flowers in three experimental greenhouse treatments: in individual pots, in flats in dense pure stands according to seed type, and in flats with the two seed types intermixed in a checkerboard array. The size distributions ofplants grown in flats were significantly more hierarchical than those of plants grown individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 40 publications
(41 reference statements)
5
76
2
Order By: Relevance
“…Because the magnitude of inbreeding depression tends to be positively associated with overall correlates of physiological stress (e.g., Waller 1985;Dudash 1990;Schmitt and Ehrhardt 1990), and physiological stress was minimized during the early stages of the plants in this study by daily watering of seedlings (during the first 2-3 weeks in flats and the first week in the field), these estimates of inbreeding depression probably err on the conservative side. Under natural conditions, seeds are set in April and May (and to a lesser extent from March to June), and germinate during the first extended rains of fall or winter, which may occur anytime between October and January.…”
Section: Environmental Effectsmentioning
confidence: 87%
“…Because the magnitude of inbreeding depression tends to be positively associated with overall correlates of physiological stress (e.g., Waller 1985;Dudash 1990;Schmitt and Ehrhardt 1990), and physiological stress was minimized during the early stages of the plants in this study by daily watering of seedlings (during the first 2-3 weeks in flats and the first week in the field), these estimates of inbreeding depression probably err on the conservative side. Under natural conditions, seeds are set in April and May (and to a lesser extent from March to June), and germinate during the first extended rains of fall or winter, which may occur anytime between October and January.…”
Section: Environmental Effectsmentioning
confidence: 87%
“…It is commonly stated that growth in higherstress conditions will cause higher inbreeding depression, and several studies have indeed found increased inbreeding depression with lower light levels (Schemske 1983) or higher plant density (Schmitt and Ehrhardt 1990;Wolfe 1993). It is probably often the case, however, that outcrossed progeny will exhibit a proportionally greater response to increasing environmental quality.…”
Section: Inbreeding Depression At Different Life Stagesmentioning
confidence: 96%
“…We may, however, also expect selection against selffertilisation, because self-fertilisation can lead to reduced ÂŽtness compared to cross-fertilisation in both animals and plants (e.g. Charlesworth and Charlesworth, 1987;Jarne and Delay, 1990;Schmitt and Ehrhardt, 1990).…”
Section: Introductionmentioning
confidence: 99%